Gender, status, and team interaction: A microdynamic exploration of wearable sensor data across 11 research groups - Jörg Müller; Alvaro Uzaheta; Julián Salas Piñón (PLoS ONE, 2026)
Diversity research is increasingly moving beyond a static focus on linear relationships between team-level diversity attributes and outcomes toward a dynamic, configurational perspective on team processes. Recent developments emphasise the structural dimensions of interpersonal relations within teams and how dyadic relationships, mutual perceptions, and behaviours shape team-level outcomes over time. Drawing on real-world organisational data, we apply a hierarchical Dynamic Actor Network Model to examine the role of gender homophily, professional status, and gender-based status cues in face-to-face interactions across 11 R&D teams. Our analysis of wearable sensor data reveals nuanced patterns that challenge any clear-cut diversity effects within teams. Although mixed‑gender interactions are generally more common, the interplay between professional status and gender‑based status cues changes across organisational contexts. Professional status shows no clear effect on interaction frequency, whereas gender‑based status effects are observed in research laboratories but not in private companies. These findings underscore the continued relevance of demographic attributes and associated status dynamics, while highlighting the value of a configurational and temporally sensitive approach to understanding team interaction.